Detecção do estado de sonolência via um único canal de eletroencefalografia através da transformada wavelet discreta - Silveira, Tiago da (2012)
Many fatal traffic accidents are caused by fatigued and drowsy drivers. In this context, automatic drowsiness detection devices are an alternative to minimize this issue. In this work, two new methodologies to drowsiness detection are presented, considering a signal obtained from a single electroencephalography channel: (i) drowsiness detection through best m-term approximation, applied to the wavelet expansion of the analysed signal; (ii) drowsiness detection through Mahalanobis distance with wavelet coefficients. The results of both methodologies are compared with a method which uses Mahalanobis distance and Fourier coefficients to drowsiness detection. All methodologies consider the medical evaluation of the brain signal, given by the hypnogram, as a reference.